Wave Propagation and Localization in a Randomly Disordered Periodic Piezoelectric Axial-Bending Coupled Beam. Issue 9 (September 2013) - Zhu, Hongping; Ding, Lan; Yin, Tao
The wave propagation and localization in periodic and randomly disordered periodic piezoelectric axial-bending coupled beams are studied in this paper. The dynamic stiffness matrix is derived based on the finite element model and the transfer matrix between two adjacent cells is obtained by using the continuity conditions. In addition, the Lyapunov exponent method is employed to calculate the localization factor characterizing the average exponential rate of decay of the wave amplitude in the disordered periodic structure. Through the comprehensive numerical simulations, the effects of different material and geometric properties as well as disordered parameters on the localization factors are investigated. The results show that wave propagation and localization in the periodic and disordered periodic piezoelectric beam can be altered by properly adjusting the structural parameters.